2020
DOI: 10.1177/1078155220918644
|View full text |Cite
|
Sign up to set email alerts
|

Successful alectinib desensitization in a patient with anaplastic lymphoma kinase-positive adenocarcinoma of the lung and alectinib-induced drug rash

Abstract: Introduction Alectinib is an oral tyrosine kinase inhibitor currently recommended by the National Comprehensive Cancer Network (NCCN) as the preferred first-line treatment option for the treatment of metastatic anaplastic lymphoma kinase (ALK) gene rearrangement-positive non-small cell lung cancer (NSCLC). Skin toxicity is a known adverse effect of this medication, yet current recommendations are unclear regarding how to best manage patients who develop severe skin toxicity while taking alectinib. Case report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…7,11 A literature review identified four cases (Table 2), of which three outlined their desensitization protocol. [7][8][9] In all four, the skin rash occurred 10-14 days of starting alectinib and did not reoccur after the desensitization protocol. There is no universal desensitization protocol.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…7,11 A literature review identified four cases (Table 2), of which three outlined their desensitization protocol. [7][8][9] In all four, the skin rash occurred 10-14 days of starting alectinib and did not reoccur after the desensitization protocol. There is no universal desensitization protocol.…”
Section: Discussionmentioning
confidence: 92%
“… 7 , 8 The restarting doses of alectinib in the other three cases were very low (20 mg, 37.5 mg and 40 mg), whereas we started at a higher dose of 150 mg twice daily. 7 9 Since alectinib comes in 150 mg capsules, we believe our starting dose was more convenient and feasible. Furthermore, considering that our patient had no prior allergies and experienced no additional complications except for a rash which completely resolved after stopping the medication, we felt it was reasonable to start at 150 mg twice daily with very close monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Severe skin rashes (Grade 3) because of alectinib treatment are rare events (0%-3%) (3,4). Table summarizes F: female, NSCLC: non-small cell lung cancer, EML4: echinoderm microtubule-associated protein-like4, ALK: anaplastic lymphoma kinase, KIF5: kinesin family member 5B, RET: rearranged during transfection, ICI; immune checkpoint inhibitor, HT1: hydroxytryptamine1, mPSL: methylprednisolone, PSL: prednisolone case reports of severe skin rash caused by alectinib (8)(9)(10)(11)(12). Erythema multiforme caused by alectinib was reported in one case by Kimura et al (8).…”
Section: Discussionmentioning
confidence: 99%